Conductive hydrogel and preparation method thereof
By soaking the dry gel in a solution of charged functional substances and salt electrolytes to form a conductive hydrogel, the problem of insufficient electrochemical reaction and mechanical properties of existing conductive hydrogels during the preparation process is solved, and the efficiency of high conductivity, mechanical strength and functional substance transdermal release is improved.
Patent Information
- Application Number
- CN202010071432.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-01-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-01-21
AI Technical Summary
During the preparation process, existing conductive hydrogels are prone to electrochemical reactions or water electrolysis, which affects their electrical conductivity and mechanical properties, and the transdermal efficiency of functional substances is low.
By providing the x-gel and soaking it in a solution of charged functional substances and salt electrolytes to swelling equilibrium, a conductive hydrogel is formed. This method improves the mechanical strength and conductivity of the conductive hydrogel, and enhances the loading of functional substances and transdermal release efficiency.
The prepared conductive hydrogel has good conductivity and mechanical properties, with large loads of charged functional substances and high transdermal release efficiency, which significantly improves its application value in the fields of flexible electronic devices, bioelectrochemical sensors and drug release.
Smart Images

Figure CN113214500B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, in particular to a conductive hydrogel and a preparation method thereof. Background Art
[0002] At present, with the development of science and technology, the flexibility, wearability and foldability of electronic products have become new development needs. Flexible materials are the basis of flexible electronic products. Among them, conductive gel has received widespread attention due to its good conductivity, flexibility and biocompatibility. Conductive gel is to add some conductive substances to the traditional gel. Conductive gel has good conductivity and has the unique three-dimensional porous structure of traditional gel. It has good flexibility and biocompatibility. Therefore, conductive gel has a wide range of application value in the fields of flexible electronic devices, bioelectrochemical sensors, drug release, etc. Hydrogel has a large surface area, adjustable pore size, moderate pore volume, and high porosity. The high specific surface area can load biomacromolecules, and the large pore size can encapsulate different types of drugs. Conductive hydrogel based on hydrogel can be used in the field of drug delivery and drug release. For example, functional substances such as drugs, active factors and natural polymers can be loaded through conductive hydrogels, and then slowly released in the human body through transdermal means to achieve the purpose of treatment or monitoring. Summary of the invention
[0003] The present invention is based on the inventor's discovery and understanding of the following facts and problems:
[0004] In the current method for preparing conductive hydrogel, gel material is usually used as substrate, and conductive materials such as conductive polymers, carbon nanotubes, graphene, graphene oxide, and metal nanoparticles are added to the gel material by blending, doping, etc. to form conductive hydrogel. In the conductive hydrogel prepared by the above method, the migration of ions and electrons is easy to occur simultaneously, and the conductive hydrogel may undergo electrochemical reactions or water electrolysis, thereby affecting the conductivity and mechanical properties of the conductive hydrogel. In addition, when functional substances such as drugs, active factors, and natural polymers are loaded in hydrogels with sustained release function, the efficacy of the functional substances will be greatly lost, and the transdermal efficiency of most functional substances is low. Therefore, if a new conductive hydrogel and its preparation method can be proposed, the conductive hydrogel prepared by the method has good conductivity and mechanical properties, and the amount of the functional substances coated in the conductive hydrogel is large, and the transdermal efficiency of the functional substances in the conductive hydrogel is high, the above problems can be solved to a large extent.
[0005] In view of this, in one aspect of the present invention, the present invention proposes a method for preparing a conductive hydrogel. According to an embodiment of the present invention, the method includes: providing a dry gel; soaking the dry gel in a first solution and soaking it until swelling equilibrium to form the conductive hydrogel, wherein the first solution contains a charged functional substance and a salt electrolyte. As a result, the conductive hydrogel prepared by the method has high mechanical strength and good conductivity, and the structure of the charged functional substance is not easily destroyed when loaded, and the loading amount of the charged functional substance is large. When the conductive hydrogel is used for transdermal release of the charged functional substance, the transdermal efficiency is high.
[0006] According to an embodiment of the present invention, in the first solution, the charged functional substance includes at least one of hyaluronic acid, glycoprotein, collagen peptide, amino acid and fatty acid; the salt electrolyte includes at least one of sodium chloride, sodium sulfate, sodium nitrate, potassium chloride, potassium sulfate, potassium nitrate and silver nitrate. Thus, when the dry gel is soaked and swelled in the first solution formed by the above materials, the charged functional substance can be well absorbed into the dry gel, and the above salt electrolyte can be well absorbed into the dry gel, and the above charged functional substance can increase the absorption amount of the dry gel to the salt electrolyte, and can improve the conductivity of the formed conductive hydrogel, and further improve the use performance of the prepared conductive hydrogel.
[0007] According to an embodiment of the present invention, in the first solution, the mass ratio of the charged functional substance to the salt electrolyte is (1-90): 1. Therefore, when the mass ratio of the charged functional substance to the salt electrolyte is within the above range, the charged functional substance can better promote the absorption of the salt electrolyte by the dry gel and improve the conductivity of the conductive hydrogel; and under the action of the electric field, the charged functional substance can be better released through the skin, and the transdermal efficiency is high.
[0008] According to an embodiment of the present invention, the xerogel is prepared by the following method: sodium alginate, acrylamide, a chemical crosslinking agent, an initiator and a catalyst are mixed to form a prepolymer solution, and the prepolymer solution undergoes a chemical reaction to form a semi-interpenetrating network hydrogel; the semi-interpenetrating network hydrogel is immersed in a second solution, the second solution contains divalent ions, and the semi-interpenetrating network hydrogel is physically crosslinked to form an ionic covalent double network hydrogel; the ionic covalent double network hydrogel is dried to form the xerogel. Thus, the method can easily prepare a xerogel with good performance, and the xerogel can be coated with more charged functional substances and salt electrolytes after swelling, and has good performance.
[0009] According to an embodiment of the present invention, the second solution includes at least one of calcium chloride, calcium sulfate, and calcium nitrate; in the second solution, the mass concentration of the calcium ions is 0.5wt%-10wt%. Thus, the above-mentioned divalent calcium ions are beneficial to the physical cross-linking of the semi-interpenetrating network hydrogel, and are beneficial to the formation of ionic covalent double network hydrogels, thereby improving the mechanical strength of the conductive hydrogel prepared by the method, and after the above-mentioned ionic covalent double network hydrogel is made into a dry gel, it is beneficial to the loading of charged functional substances, and the structure of the charged functional substances will not be destroyed during the loading process, and the loading amount of the charged functional substances is large, and the transdermal release effect of the charged functional substances under the action of the electric field is good, further improving the use performance of the conductive hydrogel prepared by the method; and when the concentration of calcium ions is within the above range, the structure of the prepared ionic covalent double network hydrogel is better, which is beneficial to the loading and transdermal release of charged functional substances, further improving the use performance of the conductive hydrogel prepared by the method.
[0010] According to an embodiment of the present invention, in the prepolymer solution, the mass ratio of the sodium alginate to the acrylamide is 1:(1-15). Thus, the performance of the conductive hydrogel prepared by the method is further improved.
[0011] According to an embodiment of the present invention, the chemical crosslinking agent includes: at least one of N,N'-methylenebisacrylamide and polyethylene glycol dimethacrylate; the initiator includes at least one of ammonium persulfate, potassium persulfate and sodium persulfate; and the catalyst includes N,N,N',N'-tetramethylethylenediamine. Thus, the performance of the conductive hydrogel prepared by the method is further improved.
[0012] According to an embodiment of the present invention, in the prepolymer solution, the molar amount of the chemical crosslinking agent is 0.01% to 0.1% of the molar amount of the acrylamide; the molar amount of the initiator is 0.005% to 0.5% of the molar amount of the acrylamide; and the molar amount of the catalyst is 0.01% to 0.15% of the molar amount of the acrylamide. Thus, the performance of the conductive hydrogel prepared by the method is further improved.
[0013] According to an embodiment of the present invention, the first solution further includes a permeation enhancer, and the permeation enhancer includes at least one of propylene glycol, glycerol, ethanol, azone, polyvinyl pyrrolidone, isopropyl alcohol, and dimethyl sulfoxide. Thus, the permeation enhancer can enhance the transdermal release effect of the charged functional substance in the conductive hydrogel, and further improve the transdermal release efficiency of the charged functional substance in the conductive hydrogel.
[0014] In another aspect of the present invention, the present invention provides a conductive hydrogel. According to an embodiment of the present invention, the conductive hydrogel is prepared by the method described above. Therefore, the conductive hydrogel has all the characteristics and advantages of the conductive hydrogel prepared by the method described above, which will not be repeated here. In general, the conductive hydrogel has good conductivity and high mechanical strength, the conductive hydrogel has a large coating amount of the charged functional substance, and the transdermal release efficiency of the charged functional substance is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0016] Figure 1 A flow chart of a method for preparing a conductive hydrogel according to one embodiment of the present invention is shown;
[0017] Figure 2 A flow chart of a method for preparing a conductive hydrogel according to another embodiment of the present invention is shown;
[0018] Figure 3 A graph showing test data of hydrogel swelling rate according to one embodiment of the present invention; and
[0019] Figure 4 A graph showing test data of water evaporation efficiency of a conductive hydrogel according to an embodiment of the present invention. DETAILED DESCRIPTION
[0020] The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0021] In one aspect of the present invention, the present invention provides a method for preparing a conductive hydrogel. The method first provides a dry gel, and then soaks the dry gel in a solution containing a charged functional substance and a salt electrolyte, soaks until swelling equilibrium, and forms a conductive hydrogel. The conductive hydrogel prepared by the method has high mechanical strength, and the conductive hydrogel simultaneously loads the charged functional substance and the salt electrolyte by the swelling absorption of the dry gel. The structure of the charged functional substance is not easily destroyed during the loading process, the structural stability is high, and the load capacity is large. In addition, the addition of the charged functional substance will increase the number of water-containing pores in the hydrogel, so that the hydrogel can absorb more ions and provide more space for ion migration. Therefore, the charged functional substance can promote the absorption of the salt electrolyte by the dry gel, and the concentration of the salt electrolyte in the conductive hydrogel can be increased, thereby improving the conductivity of the conductive hydrogel. Under the action of the electric field, the charged functional substance in the conductive hydrogel can be better released through the skin by ion pouring, and the transdermal efficiency is high.
[0022] According to an embodiment of the present invention, referring to Figure 1 , the method comprising:
[0023] S100: Provides dry gel
[0024] In this step, a dry gel is first provided. Specifically, the type and preparation method of the dry gel are not particularly limited, as long as it can swell well and absorb more charged functional substances and salt electrolytes. Figure 2 , the xerogel can be prepared by the following method:
[0025] S110: Formation of semi-IPN hydrogel
[0026] In this step, sodium alginate, acrylamide, a chemical crosslinking agent, an initiator and a catalyst are mixed to form a prepolymer solution, and the prepolymer solution undergoes a chemical reaction to form a semi-interpenetrating network hydrogel. According to an embodiment of the present invention, in the prepolymer solution, the mass ratio of sodium alginate to acrylamide can be 1:(1-15), for example, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:10, 1:12, etc. Thus, when the mass ratio of sodium alginate to acrylamide is within the above range, the crosslinking degree of the semi-interpenetrating network hydrogel formed is relatively high, which further improves the performance of the conductive hydrogel prepared by the method.
[0027] According to an embodiment of the present invention, the chemical crosslinking agent may include at least one of N,N'-methylenebisacrylamide and polyethylene glycol dimethacrylate; the initiator may include at least one of ammonium persulfate, potassium persulfate and sodium persulfate; and the catalyst may include N,N,N',N'-tetramethylethylenediamine. Thus, the performance of the conductive hydrogel prepared by the method is further improved. Specifically, in the prepolymer solution, the molar amount of the chemical cross-linking agent can be 0.01% to 0.1% of the molar amount of acrylamide, for example, it can be 0.02%, it can be 0.04%, it can be 0.05%, it can be 0.07%, it can be 0.09%, etc.; the molar amount of the initiator can be 0.005% to 0.5% of the molar amount of acrylamide, for example, it can be 0.01%, it can be 0.05%, it can be 0.08%, it can be 0.1%, it can be 0.2%, it can be 0.3%, it can be 0.4%, etc.; the molar amount of the catalyst can be 0.01% to 0.15% of the molar amount of acrylamide, for example, it can be 0.02%, it can be 0.04%, it can be 0.05%, it can be 0.06%, it can be 0.08%, it can be 0.1%, it can be 0.12%, it can be 0.14%, etc. Therefore, when the chemical crosslinking agent, catalyst and initiator are formed from the above materials and their content is within the above range, the polymerization reaction between sodium alginate and acrylamide can be better promoted to form a semi-interpenetrating network hydrogel with a high degree of crosslinking and large voids, thereby further improving the performance of the conductive hydrogel prepared by the method.
[0028] S120: Formation of ionic covalent double network hydrogels
[0029] In this step, the semi-interpenetrating network hydrogel prepared in the previous step is immersed in a second solution, the second solution contains divalent ions, and the semi-interpenetrating network hydrogel forms an ionic covalent double network hydrogel through physical crosslinking. According to an embodiment of the present invention, the second solution may include an aqueous solution containing divalent calcium ions, and specifically, the second solution may include at least one of calcium chloride, calcium sulfate, and calcium nitrate. Thus, the above-mentioned divalent calcium ions are conducive to the physical crosslinking of the semi-interpenetrating network hydrogel, are conducive to the formation of an ionic covalent double network hydrogel, improve the mechanical strength, swelling properties, etc. of the conductive hydrogel prepared by the method, and the conductive hydrogel has a very low dehydration rate, and its properties remain unchanged during use, which can extend the use time of the conductive hydrogel; and after the above-mentioned ionic covalent double network hydrogel is made into a dry gel, it is conducive to the loading of charged functional substances, and the loading amount of charged functional substances is large, and the transdermal release effect of charged functional substances under the action of an electric field is good, which further improves the use performance of the conductive hydrogel prepared by the method.
[0030] According to an embodiment of the present invention, in the second solution, the concentration of calcium ions can be 0.5wt%-10wt%, for example, 1wt%, 2wt%, 3wt%, 5wt%, 6wt%, 8wt%, etc. Thus, when the concentration of calcium ions is within the above range, the prepared ionic covalent double network hydrogel has a moderate degree of crosslinking, high mechanical strength, and a relatively moderate pore size, which is conducive to the loading and transdermal release of charged functional substances, and further improves the performance of the conductive hydrogel prepared by the method.
[0031] S130: Dry gel formation
[0032] In this step, the ionic covalent double network hydrogel prepared in the previous step is dried to form a xerogel. According to an embodiment of the present invention, the ionic covalent double network hydrogel prepared in the previous step can be dried to a constant weight to obtain a xerogel. Thus, in the subsequent steps, the xerogel can be soaked to restore its double network structure, and the charged functional substances and salt electrolytes can be well coated therein.
[0033] S200: Soaking the dry gel in the first solution until swelling equilibrium is reached to form a conductive hydrogel
[0034] In this step, the dry gel formed in the previous step is immersed in the first solution and immersed until swelling equilibrium is reached to form a conductive hydrogel, wherein the first solution contains a charged functional substance and a salt electrolyte. According to an embodiment of the present invention, in the first solution, the charged functional substance may include at least one of hyaluronic acid, glycoprotein, collagen peptide, amino acid and fatty acid, and the salt electrolyte may include at least one of sodium chloride, sodium sulfate, sodium nitrate, potassium chloride, potassium sulfate, potassium nitrate and silver nitrate. Therefore, when the dry gel is immersed and swelled in the first solution formed by the above materials, the charged functional substance can be well absorbed into the dry gel, the structure of the charged functional substance will not be destroyed during the loading process, and the loading amount of the charged functional substance is large. The above charged functional substance coated in the conductive hydrogel can be transdermally released by ion injection under the action of the electric field, and the transdermal efficiency is high; and the above salt electrolyte can be well absorbed into the dry gel, and the above charged functional substance can increase the absorption amount of the salt electrolyte by the dry gel, for example, it can increase the ion concentration of chloride ions and sodium ions in the conductive hydrogel, which can provide a large space for ion migration, can improve the conductivity of the formed conductive hydrogel, and further improve the use performance of the prepared conductive hydrogel.
[0035] According to an embodiment of the present invention, in the first solution, the mass ratio of the charged functional substance to the salt electrolyte can be (1-90):1, for example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, etc. Therefore, when the mass ratio of the charged functional substance to the salt electrolyte is within the above range, the charged functional substance can better promote the absorption of the salt electrolyte by the dry gel and improve the conductivity of the conductive hydrogel; and under the action of the electric field, the charged functional substance can be better released through the skin, and the transdermal efficiency is high. When the mass ratio of the charged functional substance to the salt electrolyte is too large, for example, greater than 90:1, the viscosity of the first solution is too large, and the dry gel absorbs less solution, resulting in poor transdermal efficiency and conductivity of the conductive hydrogel; when the mass ratio of the charged functional substance to the salt electrolyte is too small, for example, less than 1:1, the viscosity of the first solution is too small, although the dry gel absorbs more solution, the content of the charged functional substance in the solution is small, which will also result in poor transdermal efficiency and conductivity of the conductive hydrogel.
[0036] According to an embodiment of the present invention, in order to further improve the transdermal efficiency of the charged functional substance in the conductive hydrogel, the first solution may further include a permeation enhancer, for example, the permeation enhancer may include at least one of propylene glycol, glycerol, ethanol, azone, polyvinyl pyrrolidone, isopropyl alcohol, and dimethyl sulfoxide. Thus, the permeation enhancer can enhance the transdermal release effect of the charged functional substance in the conductive hydrogel, and further improve the transdermal release efficiency of the charged functional substance in the conductive hydrogel.
[0037] In summary, the conductive hydrogel prepared by this method has high mechanical strength and good conductivity. The structure of the charged functional substance is not easily destroyed when loaded, and the loading amount of the charged functional substance is large. When the conductive hydrogel is used for transdermal release of the charged functional substance, the transdermal efficiency is high.
[0038] In another aspect of the present invention, the present invention provides a conductive hydrogel. According to an embodiment of the present invention, the conductive hydrogel is prepared by the method described above. Therefore, the conductive hydrogel has all the characteristics and advantages of the conductive hydrogel prepared by the method described above, which will not be repeated here. In general, the conductive hydrogel has good conductivity and high mechanical strength, the conductive hydrogel has a large coating amount of the charged functional substance, and the transdermal release efficiency of the charged functional substance is high.
[0039] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are conventional products that can be purchased from the market.
[0040] Example 1: Preparation of Conductive Hydrogel A
[0041] (1) mixing sodium alginate, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine in a molar ratio of 1:10:0.5%:0.1%:0.5% to obtain a prepolymer solution, pouring the prepolymer solution into a mold, and reacting at room temperature to obtain a semi-interpenetrating network hydrogel;
[0042] (2) immersing the semi-IPN hydrogel formed in step (1) in an aqueous solution containing calcium chloride, wherein the concentration of calcium ions in the aqueous solution is 5%, to form an ionic covalent double network hydrogel through physical crosslinking;
[0043] (3) drying the ionic covalent double network hydrogel obtained in step (2) to a constant weight to form a xerogel;
[0044] (4) Soaking the dry gel obtained in step (3) in a first solution until swelling equilibrium is reached to form a conductive hydrogel A, wherein the first solution contains hyaluronic acid and sodium chloride, and the mass ratio of hyaluronic acid to sodium chloride is 20:1.
[0045] Example 2: Preparation of Conductive Hydrogel B
[0046] The other preparation methods are the same as those in Example 1, except that the mass ratio of hyaluronic acid and sodium chloride added in step (4) is 100:1 to form conductive hydrogel B.
[0047] In the same way, the dry gel sample obtained in step (3) was weighed at room temperature and placed in the first solution (PH=7.4) in Example 2, and soaked for 24 hours until the hydrogel reached swelling equilibrium, the gel was taken out and the residual water on the surface of the hydrogel sample was completely absorbed and removed with filter paper, and then the swollen hydrogel was weighed. After testing and calculation, it was found that the swelling rate of the conductive hydrogel B in Example 2 was 550%. It can be seen that when the mass ratio of hyaluronic acid and sodium chloride (i.e., the mass ratio of the charged functional substance and the salt electrolyte) is in the range of (1-90):1 as mentioned above, the swelling rate of the conductive hydrogel is high, and thus the conductivity and transdermal efficiency are high.
[0048] 2. Hydrogel water evaporation rate test
[0049] The sample of conductive hydrogel A prepared in Example 1 was weighed and recorded as M1; then the sample of conductive hydrogel A was placed at room temperature, and the hydrogel was taken out at a prescribed time interval to measure its weight M2. Each group of experiments was repeated three times. The water evaporation rate of the hydrogel was calculated according to the following formula:
[0050]
[0051] Test result reference Figure 4 The test results show that the hydrogel has a strong water retention capacity at room temperature, and the hydrogel still holds 50% water after 140 hours. Therefore, the conductive hydrogel prepared in this application has a strong water retention capacity, which can ensure that the use period of the conductive hydrogel is within 5 days, and the use performance of the conductive hydrogel is good.
[0052] 3. In vitro hydrogel transdermal release rate test
[0053] The conductive hydrogels prepared in Example 1 and Example 2 were respectively evenly distributed on the surface of mouse skin, and a forward voltage was applied to the hydrogels, and the amount of the released charged functional substance hyaluronic acid was tested using a colorimetric reagent. The test results show that the efficiency of the in vitro transdermal release of the conductive hydrogel in Example 1 can reach more than 30%, and the efficiency of the in vitro transdermal release of the conductive hydrogel in Example 2 is about 3.4%, proving that the transdermal release efficiency of the charged functional substance in the conductive hydrogel prepared by the method of the present application is high, especially when the mass ratio of hyaluronic acid to sodium chloride (i.e., the mass ratio of the charged functional substance to the salt electrolyte) is in the range of (1-90):1 as described above, the transdermal efficiency of the conductive hydrogel is high. When the mass ratio of hyaluronic acid to sodium chloride is too large, the viscosity of the solution is too large, and the transdermal release effect is poor.
[0054] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0055] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a conductive hydrogel, characterized in that: include: providing a xerogel; Soaking the dry gel in a first solution until swelling equilibrium is reached to form the conductive hydrogel, wherein the first solution contains a charged functional substance and a salt electrolyte; In the first solution, the charged functional substance includes at least one of hyaluronic acid, glycoprotein, collagen peptide, amino acid and fatty acid; The salt electrolyte includes at least one of sodium chloride, sodium sulfate, sodium nitrate, potassium chloride, potassium sulfate, potassium nitrate, and silver nitrate; In the first solution, the mass ratio of the charged functional substance to the salt electrolyte is (1-90): 1; The dry gel is prepared by the following method: Mixing sodium alginate, acrylamide, a chemical crosslinking agent, an initiator and a catalyst to form a prepolymer solution, wherein the prepolymer solution undergoes a chemical reaction to form a semi-interpenetrating network hydrogel; Soaking the semi-IPN hydrogel in a second solution, wherein the second solution contains divalent ions, and the semi-IPN hydrogel forms an ionic covalent double network hydrogel through physical crosslinking; The ionic covalent double network hydrogel is dried to form the xerogel.
2. The method according to claim 1, characterized in that The second solution includes at least one of calcium chloride, calcium sulfate, and calcium nitrate; In the second solution, the mass concentration of calcium ions is 0.5wt%-10wt%.
3. The method according to claim 1, characterized in that In the prepolymer solution, the mass ratio of the sodium alginate to the acrylamide is 1:(1-15).
4. The method according to claim 1, characterized in that: The chemical cross-linking agent includes: at least one of N,N'-methylenebisacrylamide and polyethylene glycol dimethacrylate; The initiator comprises at least one of ammonium persulfate, potassium persulfate and sodium persulfate; The catalyst includes N,N,N',N'-tetramethylethylenediamine.
5. The method according to claim 4, characterized in that In the prepolymer solution, the molar amount of the chemical crosslinking agent is 0.01% to 0.1% of the molar amount of the acrylamide; the molar amount of the initiator is 0.005% to 0.5% of the molar amount of the acrylamide; and the molar amount of the catalyst is 0.01% to 0.15% of the molar amount of the acrylamide.
6. The method according to claim 1, characterized in that The first solution further includes a permeation enhancer, and the permeation enhancer includes at least one of propylene glycol, glycerol, ethanol, azone, polyvinyl pyrrolidone, isopropyl alcohol, and dimethyl sulfoxide.
7. A conductive hydrogel, characterized in that: The conductive hydrogel is prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ion-covalent double-network hydrogel and preparation method thereof
CN105461945A